Al-Baqillani’s Critique to Anthropomorphist’s Concept of The Attributes of God - Much Hasan Darojat; Mohd Fauzi Hamat; Wan Adli Wan Ramli (Universiti Sains Islam Malaysia, 2024)
This article aims to delineate al-Baqillani’s responses to the Anthropomorphists regarding their views on the attributes of God. As an Ash‘arite, al-Baqillani disproved some theological doctrines formulated by this group in dealing with a number of theological topics; the speech of God, the Quran and its characteristics, and other attributes of God. He obviously shows his capacity and attempts to maintain the mainstream of Ash‘arites’ theological framework. Through this study, the author concludes that his theological position takes the combination between rationalistic method and application of the revelation. This research applied a textual analysis approach, using descriptive and analytical methods to investigate and analyze primary sources related to the issues. It also adopts the historical method to scrutinize several events on the subject.